Serum zinc, copper and ferritin levels in transfusion dependent thalassemia patients with iron chelator therapy - Munira, Fatema Tuz; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2019)
Background: Transfusion dependent thalassemia (TDT) patients require regular blood transfusion and iron chelator therapy to maintain their life. Iron chelator may alter serum zinc and copper level in TDT patients. Objective: To observe serum zinc and copper and ferritin levels in transfusion dependent thalassemic patients treated with iron chelator. Method: The present cross sectional study was carried out in the department of Physiology, BSMMU, Dhaka between September 2017 to February 2019. Thirty cases of TDT, aged 5-40 year were included in the study group. Age and sex matched 30 healthy subjects were also studied as control. All the TDT patients were selected from the outpatient Department of Hematology and Transfusion Medicine, BSMMU, Dhaka. Serum zinc was measured by Spectrophotometric method and serum copper and ferritin levels were measured by colorimetric method. For statistical analysis independent sample t test was used. Result: The mean serum zinc level was significantly (p<0.05) lower and serum ferritin level was significantly (p<0.001) higher in TDT compared to control. Again, mean serum copper level and Zn/Cu ratio were not significantly (p>0.05) different in study groups compared to that of control. In addition, 3.3 % TDT patients had hypozincemia and 13.3% TDT patients had hypercupremia. Conclusion: This study may conclude that low serum zinc level and high copper level may be associated with TDT patients treated by combined deferoxamine (DFO) & deferiprone (DFP) iron chelator. J Bangladesh Soc Physiol. 2019, June; 14(1): 38-42